The normal heart - Murphy, Ryan, 1965-; Ruffalo, Mark; Bomer, Matthew, 1977-; Kitsch, Taylor, 1981-; Kramer, Larry ([Place of publication not identified] : HBO Home Entertainment, 2014)
Tells the story of the early days of the HIV-AIDS crisis in New York city in the early 1980's as seen through the eyes of writer and activist Ned Weeks, the founder of a HIV advocacy group.
Based on the play by Larry Kramer.
Dolby digital 5.1, anamorphic wide screen 1.78:1.
Features: extended cut of "How to start a war," behind-the-scenes featurette offering interviews, digital copy of the film.
Mark Ruffalo, Matt Bomer, Taylor Kitsch, Jim Parsons, Julia Roberts.
Originally broadcast on television in 2014.
TV rating: Not rated.
Keywords: Kramer, Larry -- Film adaptations; AIDS (Disease) -- Drama; AIDS (Disease) -- Patients -- Drama; Gay activists -- Drama; Gay men -- Drama; Made-for-TV movies; Television programs; Video recordings for the hearing impaired; Based on the book